Compensation, Competency and Motivation as Determiners of The Performance of Financial Administrative Officers - Purwanto, Arief; Nirma, Nirma; Mas, Nasharuddin (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study explains the effect of compensation, competency, and motivation on employee performance directly and indirectly. The method used is quantitative - explanatory. The sample is 33 Financial Administration Officers (PPK) in Pasuruan City. Data analysis using SEM-PLS. The results showed that compensation can increase motivation. However, it has not been able to improve performance. Furthermore, competence can increase motivation and be able to improve performance. On the other hand, motivation can improve performance. Other results, indirectly it is known that motivation has not been able to mediate the relationship between compensation and performance. In addition, motivation is able to mediate the relationship between competence and performance